2015
DOI: 10.1007/s11165-015-9476-8
|View full text |Cite
|
Sign up to set email alerts
|

Taking on the Heat—a Narrative Account of How Infrared Cameras Invite Instant Inquiry

Abstract: Integration of technology, social learning and scientific models offers pedagogical opportunities for science education. A particularly interesting area is thermal science, where students often struggle with abstract concepts, such as heat. In taking on this conceptual obstacle, we explore how hand-held infrared (IR) visualization technology can strengthen students’ understanding of thermal phenomena. Grounded in the Swedish physics curriculum and part of a broader research programme on educational uses of IR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 56 publications
1
27
0
1
Order By: Relevance
“…Many other examples of experimental technologies used in science or engineering settings that provide different affordances could have been chosen, and I maintain that in many other (if not all) cases, what is possible to discern depends on the technology used. For example, Haglund et al (2015) have demonstrated how new cheap infrared cameras make it possible to carry out experiments in thermodynamics that gave immediate results, and Bernhard (1999) has demonstrated how probeware technologies enable the visualisation of oscillation modes in coupled harmonic oscillators. In both of these examples, the technologies make it possible to visualize in experiments phenomena and concepts that are impossible or difficult to discern with a "naked eye" (although some heat phenomena in thermodynamics experiments can, of course, be discerned somewhat rudimentarily with a "naked hand").…”
Section: Validity and Limitations Of The Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many other examples of experimental technologies used in science or engineering settings that provide different affordances could have been chosen, and I maintain that in many other (if not all) cases, what is possible to discern depends on the technology used. For example, Haglund et al (2015) have demonstrated how new cheap infrared cameras make it possible to carry out experiments in thermodynamics that gave immediate results, and Bernhard (1999) has demonstrated how probeware technologies enable the visualisation of oscillation modes in coupled harmonic oscillators. In both of these examples, the technologies make it possible to visualize in experiments phenomena and concepts that are impossible or difficult to discern with a "naked eye" (although some heat phenomena in thermodynamics experiments can, of course, be discerned somewhat rudimentarily with a "naked hand").…”
Section: Validity and Limitations Of The Resultsmentioning
confidence: 99%
“…Hewson and Hewson 1984) in the same situation. Indeed, the lab to investigate motion in an inclined plane using probeware was designed using POE theory, according to Thornton (2008), while Haglund et al (2015) have based thermodynamics learning tasks on POE-sequences. Furthermore, as experimental technologies as mediating technologies strongly influence figure-background relationships, i.e.…”
Section: Validity and Limitations Of The Resultsmentioning
confidence: 99%
“…10,11 Haglund and colleagues have conducted a series of studies on grade 4-12 students' use of IR cameras in physics teaching. [12][13][14] In practical predict-observe-explain exercises, 15 students have focused on heat conduction, and the conundrum that metals feel cool in room temperature. Apart from providing the opportunity to seeing taught thermal phenomena, students have been found to engage in 'instant inquiry' with IR cameras, in which they ask 'what-ifs' and get immediate response in real time.…”
Section: Basic Facts Of Ir Camerasmentioning
confidence: 99%
“…In a four-year research program focused on investigating how thermal imaging can support science learning in primary and secondary schools, a suite of IR-camera-based laboratory activities have been developed to target the Swedish grade 4-12 physics curricula [13,14,15,16]. The activities build on the widely-adopted predict-observe-explain (POE) approach [17], where students are asked to predict what will happen in an experiment, carefully observe as the experiment unfolds, and then explain what they observed and reconcile their observations with their predictions when there is a discrepancy.…”
Section: Infrared Cameras Accelerate Inquiry In Primary and Secondarymentioning
confidence: 99%
“…Subsequently, two grade-4 classes (9 to 10-year-olds) were introduced to such a heat transfer model. They conducted a series of IR-camera experiments, including the wood vs. metal task and the pouring of hot water into cups with different wall thicknesses and materials [14] (Fig. 3).…”
Section: Infrared Cameras Accelerate Inquiry In Primary and Secondarymentioning
confidence: 99%